The Expert And The Networked Public: Professional And Amateur Wedding Photographers In The Facebooked Wedding - Ribak, Rivka; Fridman-Naot, Dina (AoIR Selected Papers of Internet Research, 2017)
A typical middle class wedding in Israel is documented by roughly 3000-6000 still photos taken by a networked public of friends, family, service providers and professional photographers; they are uploaded and shared throughout the ceremony, and archived thereafter in various online, offline and printed photo albums. Conceiving of the wedding as a paradigmatic site of cultural production and reproduction, this paper explores the practices through which professional photographers distinguish themselves from amateurs just as digital photography became ubiquitous. Drawing on ethnographic interviews with wedding photographers and newlywed couples and an analysis of Facebook pages of wedding photographers and newlywed groups, we will suggest that as independent, "artisanal photographers" (Frosh, 2017) whose livelihood depends on direct sales to the market, wedding photographers managed to distinguish themselves from the networked public of amateur photographers by upskilling professionally (friending and coaching in addition to documenting); technologically (displaying superior equipment); and artistically (mastering the staged-authentic style). Yet in Facebook's wedding circuit economy, their work remains precarious.